Pengaruh Pandemi Covid – 19 Terhadap Ketersedian Beras di Kota Medan - Simbolon, Ramses (Universitas Katolik Santo Thomas Medan, 2025)
This study aims to determine: (1) The impact of the Covid-19 pandemic on the availability of rice in Medan City, (2) Explain the conditions of rice availability in Medan City before and during the Covid-19 pandemic and (3) Explain the negative impact of Covid-19 on the availability of rice in Medan City. This study was conducted in Medan City, North Sumatra with descriptive analysis. This study uses secondary data such as population, Number of Rice Field Areas in Medan City, Number of Rice Harvests, Imports, Exports, Stocks and Rice Production in Medan City. Data was taken for 4 years, starting from 2019 to 2022. Data sources from the Central Statistics Agency of North Sumatra Province, the Central Statistics Agency of Medan City, the Food Security Service, Agriculture of Medan City, Perum Bulug Medan City and supplemented with several literature related to this study. The results of the study show that the need for rice consumption has increased every year during the Covid-19 pandemic. Based on the collection of documents of the Medan City Food Balance Update Report, the condition of the level of rice supply during and before the Covid-19 pandemic fluctuated, but the condition of the level of rice supply during the Covid-19 pandemic in 2021 experienced a shortage. Based on the research results, the author assumes that the amount of rice needed in Medan City can be met by areas around Medan City and outside North Sumatra. This is confirmed by the results of written interviews at the Medan City Food Security Service, namely Deli Serdang, Asahan, Toba, Serdang Bedagai and Langkat for areas around Medan City, while for areas outside North Sumatra are Java, Aceh, and Sulawesi. During the Covid-19 pandemic, the availability condition experienced a surplus. The impact of the Covid-19 pandemic on the availability of rice in Medan City in terms of imports and rice stocks has increased every year, while in terms of rice production it has fluctuated.